Investigating the association between tinnitus severity and symptoms of depression and anxiety, while controlling for neuroticism, in a large middle-aged UK population. (September 2015) - McCormack, Abby; Edmondson-Jones, Mark; Fortnum, Heather; Dawes, Piers D; Middleton, Hugh; Munro, Kevin J; Moore, David R
Abstract Objective: Clinical studies indicate increased risk for depression and anxiety among tinnitus patients. However population data are scarce, and no studies have controlled for neuroticism. We examined associations between tinnitus and symptoms of depression and anxiety in a large UK population, controlling for neuroticism, to explore whether neuroticism, as previously reported, fully explains the association between symptoms of depression and anxiety, and tinnitus. Design: We used the UK Biobank resource. Study sample: 171 728 participants answered hearing questions. Results: Using generalized linear modelling, we examined associations between tinnitus (mild to severe) and symptoms of depression and anxiety. Controlling for neuroticism, patients with severe tinnitus were at increased risk of depression (odds ratio (OR) = 1.27) and anxiety (OR = 1.11) symptoms, compared to those without tinnitus. Conclusions: Although it is not possible to determine whether tinnitus is a predisposing factor to depression, these results suggest an association. We suggest further exploration to determine the clinical significance of this association. Early psychosocial intervention aimed at reducing anxiety and depression in patients at increased risk might influence the extent to which tinnitus is experienced as troubling, and therefore psychological distress associated with it. Likewise, with tinnitus patients, assessment for anxiety/depression should be considered.